Cytotoxic activity of peripheral blood lymphocytes in children with infectious mononucleosis - N. R. Slepicheva; O. I. Urazova; V. V. Novitsky; A. P. Pomogayeva (Бюллетень сибирской медицины)
Twenty children aged 3—6 years with Epstein—Barr-virus-induced infectious mononucleosis (IM) were examined. The present study is aimed at investigating the functional activity of cytotoxic lymphocytes in children with IM during clinical and hematological manifestation of the disease and early reconvalescence phase. For analyzing the subpopulation composition of peripheral blood lymphocytes in children with IM the CD-receptors on cell surfaces (CD8, CD16) were defined; for estimating apoptosis the amount of CD95-, CD95L- and annexin V-positive lymph cells (immunofluorescence method) was assessed. For determination of TNFα concentration in cultural supernatants the solid-phase immunoenzyme method was applied. It was defined that clinical and hematological manifestation of IM is accompanied by increase in the amount of CD8-, CD16-lymphocytes in blood and activation of Fas-dependent apoptosis of lymphocytes that is preserved in early reconvalescence period. Here limitation of lymphocytic cytotoxicity results from a decrease in TNFα secretion.